Estrategias Metodológicas De Estimulación Musical Y Su Incidencia En El Desarrollo De La Expresión Oral De Los Estudiantes Del Centro Educativo “Yiréh” Del Cantón Ventanas Provincia De Los Ríos - Magallanes Rodríguez Juan Samuel (2015)
At present musical activities are being introduced in education from ages because the aid is in its intellectual, auditory, sensory and speech development, use this resource to develop language and oral expression it is essential, improving capabilities of children during their developmental stage, the research aims to determine the methodological strategies musical stimulation, teachers provide a starting point for working with music in the development of student speaking, because scientific evidence supports the music develops cognitive activity and increases creativity, improving psychomotor development. In the school Yiréh shows that teachers at the primary level have not given importance to musical expression and auditory stimulation in their planning, only work auditory stimulation to teach students songs, or to gain control over them, in this institution the process teaching and learning is aimed at stimulating other areas such as motor skills, giving greater emphasis on literacy and mathematics, to the detriment of teaching that brings music, so the problem of how arose affecting the methodological strategies of musical stimulation in the development of oral expression of students in justifying this research because it will be the product of real information of the educational act benefiting the teaching-learning process. The overall objective to determine the impact of methodological strategies of musical stimulation in the development of oral expression of students in first and second year of general education basic del Education Center Canton Yiréh Windows was raised, Los Rios 2013-2014 school year, Study variables being the methodological strategies musical stimulation and development of oral expression. The research was qualitative way, the type of research, applied field, descriptive methods, interpretive, inductive, deductive, techniques for gathering information are surveys, observation and interviews, concluding that teachers are aware that methodological strategies musical stimulation favors the development of oral expression of students ,, recommending the design and implementation of a guide for teachers to implement methodological strategies musical stimulation, as strategic support in the development of their classes.